A rare case of ovarian hyperstimulation with torsion presenting with hypothyroidism - Balasubramanian, Kruthiga Kumari; Arunachalam, Pavai (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
A thirteen years old female child, who was recently diagnosed with hypothyroidism and polycystic ovary and under thyroid supplements, presented with acute abdominal pain of one day duration. Examination showed pallor with rough skin, hypotension (70/40 mmHg) and distended abdomen. Abdomen was tense with tenderness and guarding. Urgent contrast CT abdomen showed bilateral polycystic ovaries with left ovarian torsion and hemo-peritoneum. Blood investigations showed anemia (6.0 g/dL) and TSH >100 microIU/ml. She was stabilized with Intravenous fluids, packed red blood cells and taken up for surgery. Laparoscopy confirmed the diagnosis and detorsion with deroofing of cysts was done. A post-operative diagnosis of Van Wyk Grumbach syndrome - Hypothyroidsm with ovarian hyper stimulation syndrome with hemorrhagic torsion of left ovary was made. She withstood procedure well and was stable. She was discharged to a local hospital after 2 days of surgery. She is on thyroid supplements and doing well.